Upaya Meningkatkan Hasil Belajar Bahasa Inggris Aspek Reading Skill Ability Melalui Pronounciation Word By Word di SD Muhammadiyah 2 Parepare - Hadiwaratama R Jusran (Universitas Pendidikan Mandalika, 2022)
This study aims to improve learning outcomes in English aspects of reading skill ability through the word by word pronunciation learning method. This classroom action research was conducted in two cycles. The subjects of this study were fourth grade students of SD Muhammadiyah 2 Parepare with a total of 10 people. The data collection technique of this research used observation, tests, and field notes. While the data analysis technique used descriptive analysis. The results of this study indicate that the increase in learning for fourth grade students of SD Muhammadiyah 2 Parepare through pronunciation word by word is in the first cycle in the low category with an average score of 53.00, while in the second cycle there is an increase in the high category with an average value. average 85.00. In connection with these results, it can be concluded that the learning method of pronounciation word by word can improve learning outcomes of English aspects of reading skill ability for fourth grade students of SD Muhammadiyah 2 Parepare.